Strangers in the archive : literary evidence and London's East End - Kaufman, Heidi, 1969- (Victorian literature and culture series., 2022)
"Strangers in the Archive shows how understudied print and material records can expand and reshape our understanding of the East End--a place constructed in popular nineteenth-century novels and newspapers as a ghetto space overpopulated by dangerous immigrants and serial killers. A blending of scholarly memoir and literary analysis, and using Polack's Fiction without Romance as a point of entry, this book investigates the work of archives and the reach of East End Jewish literary culture throughout the Atlantic world, while drawing from digital humanities methods to expand concepts of literary evidence"--